The Assessment of Grief in Refugees and Post-conflict Survivors: A Narrative Review of Etic and Emic Research - Killikelly, Clare; Bauer, Susanna; Maercker, Andreas (Frontiers in Psychology, 2018)
Background: Prolonged Grief Disorder (PGD) is a new mental health disorder that will be recognized by the World Health Organization’s disorder classification, the ICD-11, in 2018. Current assessment measures of PGD are largely based on North American and European conceptualizations of grief (etic i.e. from the perspective of the observer). However, research is emerging from communities outside of the Global North, in particular, conflict-exposed communities, exploring local models (emic i.e. from within the cultural group), assessment measures and symptoms of grief. Several reviews have found that refugees have higher rates of mental illness, defined by etic standards as depression, post-traumatic stress disorder (PTSD), anxiety disorders and psychotic symptoms. Yet, presently there are no reviews documenting the assessment of PGD in refugees and post conflict survivors. Method: This narrative review will provide an overview of studies that assess grief in refugees to 1) identify current assessment measures of grief in refugees (ie. type and frequency of questionnaires used, whether Global North-based, etic, or locally develop, emic, and the level of cultural adaptation) and 2) to document the variety and rate of grief symptoms identified with Global North standard measures and/or local measures (i.e. the endorsement of standard symptom items and the identification of culturally specific symptoms of grief). Results: This review revealed 24 studies that assessed disordered grief in refugee or post conflict samples. Studies where heterogeneous in their assessment methods; the majority (n=17) used an etic approach, four used a combined etic/emic approach, and three used a predominantly emic approach. The rate of disordered grief was high depending on cultural adaptation approach (31-76%) and when standard etic measures were used the disordered grief rate was 32%. Conclusion: These findings will help to guide future studies to provide accurate assessment of grief in refugee and post conflict populations and has implications for improving cultural knowledge in clinical practice.